ANALYSIS OF THE RELATIONSHIP ANEMIA AND POSTPARTUM HEMORRHAGE IN ABDUL MOELOEK HOSPITAL, LAMPUNG CITY - Primasari, Sefria Indah (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
The high prevalence of anemia affects almost all age groups in society. One of the groups of people with a high prevalence is pregnant women in various countries including Indonesia, reporting that the prevalence of anemia in the world is estimated at 30% of the world's population and around 500 million people are believed to suffer from anemia. Pregnancy anemia is called